(3MGTjI OGhO Ydi TQM GdTeSjIs - (3bQI OGhO, b (B8 (3g`s ((3YHO Gddg Hf Nda GdUHGQs)
(3ChdgG (B:s
(3HSe Gddg (B.. (3bGd GdeUfa (B: (3hQJHJg Ydi ebOeI hKdGK ebGdGJ hNGJeI , GYde Cf GdeUfa QMeg Gddg bGd aCTGQ Edi (B... (3HJMQjQ cJGH cPG hcPG Ke bGd aHGOQJ Edi fbJVi GTGQJg hSejJg HGdQSGdI GdTeSjI aj GdbhGYO GdefWajI (B...s
(3BNQgG (B:s
... (3jSJfHW dg efg JYQja hGdMGUd Gf ebUO GdJYQja VefG hjQO Ydjg Cf GdebGe jOd Ydi bUO GdJYQja XGgQG Cj jbJVj bUO GdJYja XGgQG hUQjMG VefG agh dG jdGFe GdebGe (B.. (3Je GdcJGHs
(3JHUQI GdeDda (B:s
(3jbhd MGLj NdjaI (B: (3GdfSHI Edi(B: (3OGhO Hf ceGd GdbhLhj(B: (3ZdW(B. (3hGdUhGH (B: (3d bQg OGhO ef JdGePI SYO GdOjf eSYhO Hf YeQ GdJaJRGfj J (B793 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf (B2\ 1063s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdadSaI hGdefWbs